1992
DOI: 10.1111/j.1468-2273.1992.tb01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Student Loans: The Failure to Consolidate an Emerging Political Consensus

Abstract: This article contends that over a long period of time there was growing support for a student loan scheme. In the event, the Thatcher Government adopted proposals which failed to consolidate that emerging consensus. What was it about the Government's legislation that achieved this political own goal? How can such politically maladroit behaviour be explained? What elements should the legislation have contained if the consensus were to be firmed up and enhanced? These are the key questions which we attempt to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…There are indications in government statements that the proposed effect of student loans on student culture was not only an end in itself, but was also intended to have wider implications for higher education (Farrell and Tapper, 1992). In the parliamentary debate on student loans John MacGregor alluded to this when he suggested that if students saw that they were investing a small part of their own money in their higher education, then: .…”
Section: Introductionmentioning
confidence: 99%
“…There are indications in government statements that the proposed effect of student loans on student culture was not only an end in itself, but was also intended to have wider implications for higher education (Farrell and Tapper, 1992). In the parliamentary debate on student loans John MacGregor alluded to this when he suggested that if students saw that they were investing a small part of their own money in their higher education, then: .…”
Section: Introductionmentioning
confidence: 99%
“…The participants confirmed the general views of Molesworth et al (2011), agreeing that the student-as-consumer concept has been embraced on a foundation of marketisation. Specifically, they unanimously attributed the rise in consumerism to the rise in student-funded tuition fees, confirming the views of Farrell and Tapper (1992) Brown andCarasso (2013), McGettigan (2013) and Palfraymen and Tapper (2014;. Some participants had also experienced similar complaints to those identified by Bunce (2017), implying that paying nine-thousand pounds a year justified a higher standard of service.…”
Section: Oh But I Pay £9000 a Year For This…"mentioning
confidence: 66%
“…However, the Robbins committee's efforts were criticised for a lack of consideration of the implications associated with mass expansion, such as student finance (Moser, 1988). Despite this, many academics consider the various government policies introduced in the 1990s to be the most significant catalysts of consumerism (Molesworth, Scullion and Nixon, 2011;Brown, 2015), particularly the introduction of tuition fees (Farrell and Tapper, 1992;Brown and Carasso, 2013;McGettigan, 2013;Palfraymen and Tapper, 2014;. It is on this foundation of consumerism, largely created by the introduction of tuition fees, that the student-consumer concept has been embraced (Molesworth, Scullion and Nixon, 2011).…”
Section: Part Imentioning
confidence: 99%
See 2 more Smart Citations